CpG-free plasmids confer reduced inflammation and sustained pulmonary gene expression. - Hyde, Stephen C.; Pringle, Ian A.; Abdullah, Syahril; Lawton, Anna E.; Davies, Lee A.; Varathalingam, Anusha; Nunez-Alonso, Graciela A.; Green, Anne Marie; Bazzani, Reto P.; Sumner-Jones, Stephanie G.; Chan, Mario; Hong, Yu Li; et al. (Nature Publishing Group, 2008)
Pulmonary delivery of plasmid DNA (pDNA)/cationic liposome complexes is associated with an acute unmethylated CG dinucleotide (CpG)-mediated inflammatory response and brief duration of transgene expression. We demonstrate that retention of even a single CpG in pDNA is sufficient to elicit an inflammatory response, whereas CpG-free pDNA vectors do not. Using a CpG-free pDNA expression vector, we achieved sustained (≥56 d) in vivo transgene expression in the absence of lung inflammation.